(untitled) (Research, Society and Development, 2020)
This study aims to determine the water content conditions, temperature and safe storage time for maintaining the quality of stored canola seed. The seeds were stored for 180 days, the water content of 8, 10, 12 and 14%(w.b.), at temperatures of 7, 17 to 27°C. At the beginning and every 45 days of storage up to 180 days, were carried out germination test, first count of germination test, electrical conductivity test and accelerated aging test of canola seed. The percentage of germination and accelerated aging decreased significantly during storage for samples with 12 and 14% water content, stored at 17 and 27ºC. With the increase of the water content and storage temperature, an increase in the electrical conductivity of the seed. Thus, temperatures of 17 to 27 °C cause major reductions in seed quality stored at 12 and 14% water content. The temperature of 7ºC allows a better conservation of the seed water content of 8, 10 and 12% stored for 180 days.